Kondisi Fisik Atlit Shoto-kai Pemerintah Riau - yuga, Gde Ananta Yuga Mediarta (Pusat Pengembangan Olahraga Universitas Pahlawan, 2023)
After all data has been collected and processed, because this type of research is descriptive, the analytical technique that can be used is to use frequency distribution techniques (descriptive statistics) with percentage calculations, as explained by Arikunto, (1990),